Critical History Pedagogy Framework for Developing Historical Consciousness in Indonesian History Education - Nabella Angellita Setiyono; Suryo Ediyono (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
History learning in Indonesia remains largely transmissive and focused on factual memorization, limiting the development of students’ historical consciousness. This library research examines the relevance and integration of critical philosophy approaches in Indonesian history education by analyzing the canonical works of Freire, Habermas, Gadamer, and Rüsen alongside 24 peer-reviewed journal articles on history education and historical consciousness published between 2020 and 2024. Using content analysis and inter-theoretical comparison of 28 sources, the study argues that critical pedagogy, critical theory, and hermeneutics provide a coherent epistemological foundation for transforming history learning from knowledge transmission toward the cultivation of critical-historical consciousness. Its conceptual contribution is a four-pillar Critical History Pedagogy Framework comprising: deconstruction of singular narratives, democratic historical dialogue, historical-contemporary connection, and historical identity reflection. Grounded in the Merdeka Curriculum context and aligned with Rüsen’s typology of historical consciousness, this framework offers an integrated and operationalizable model for history curriculum development and pedagogy in Indonesia. Empirical testing in classroom settings is recommended for future research.